KEPEMIMPINAN KEPALA SEKOLAH DALAM RANGKA MENINGKATKAN KINERJA GURU DAN MUTU LULUSAN DI SMP NEGERI 18 DAN SMP NEGERI 28 BANDUNG - Mamun, Mohamad Agus; Wasliman, Iim; Iriantara, Yosal (2020)
Principal leadership is very important in improving teacher performance and the quality of learning at SMPN 18 and SMPN 28 Bandung. This study aims to determine: (1) How is the principal's leadership in improving teacher performance and the quality of learning at SMPN 18 and SMPN 28 Bandung (2) What are the obstacles to the principal's leadership in improving teacher performance and the quality of learning at SMPN 18 and SMPN 28 Bandung ( 3) What are the efforts of the principal in improving teacher performance and quality of learning at SMPN 18 and SMPN 28 Bandung. This research is a descriptive qualitative research, the data collected through the method of observation, interviews, documentation, triangulation, and analyzed using descriptive analysis techniques. This study aims to determine the principal's leadership in improving teacher performance and quality of learning, knowing the constraints of principal leadership in improving teacher performance and learning quality and knowing the principal's efforts to improve teacher performance and learning quality. In this research study, it shows that: (1) The leadership of the principal in improving the quality of learning at SMPN 18 and SMPN 28 Bandung is quite good. Principals are maternal, skilled in communication and easy to get along with others, assertive and democratic. (2) Obstacles to the leadership of the principal in improving the quality of learning are limited teachers and educational personnel and poor learning infrastructure. (3) The principal's effort to improve the quality of learning at SMPN 18 and SMPN 28 Bandung is to increase teacher professionalism, supervise and motivate teachers and educational staff. From the results of these studies, the authors provide suggestions to SMPN 18 and SMPN 28 Bandung to recruit educators with Masters education and new educational staff, improve learning infrastructure and improve learning achievement at SMPN 18 and SMPN 28 Bandung